As You Are Now : Post-Dramatic Theatre in Ireland (2009 – 2014) - Donnelly, Paul Brendan (Trinity College (Dublin, Ireland). School of English, 2016)
In recent years, post-dramatic theatre in Ireland has transitioned from a fringe practice to a consistent feature of annual venue programmes and curated festivals. This thesis investigates the emergence of this theatrical form, asking why post-dramatic theatre emerged to such an extent during the period in question and what aspects of theatre are particular to the form. This research is organised thematically, first locating post-dramatic theatre in a theoretical and practical context, before considering post-dramatic theatre practice through elements of performance, spectatorship, space, and text. A thematic approach makes it possible to engage with points of intersection between postmodern experience and post-dramatic forms, where multiplicity, fragmentation and incoherence are rife. It also allows for a neater analysis of these individual components in their own right.
Keywords: English, Ph.D.; Ph.D. Trinity College Dublin